The legal nature of the crime of inciting civil war or sectarian conflict and protection from it (Eurasian Journal of Humanities and Social Sciences, 2022)
The crime of inciting civil war or sectarian conflict is an independent crime that has its own concept, and the Iraqi law considers it in the Penal Code as one of the crimes against the inner security of the state. As for the Anti-Terrorism Law, it considers it a terrorist crime due to its extreme danger to the security of society because of what it entails of inciting terror and panic, and the emergence of a danger that threatens society, its institutions, and the lives of citizens. Protecting society from this lies in its criminalization by criminal protection for the internal security of the state and criminal protection for national unity and social peace, as the crime of provoking civil war or sectarian strife in its content represents an attack on higher interests in the state, as it disturbs the serenity of national unity and social peace among the various components of society and is described as a dangerous crime, as the legislators tend to criminalize the attack on the interest that he deems worthy of the protection of the criminal law and imposes punishment on the perpetrators, even if the actual harm to the protected interest is not achieved.